Pengaruh Daya Tarik Wisata, Promosi Digital dan Fasilitas Terhadap Minat Berkunjung Wisatawan di Objek Wisata Taman Kelapa Pandan Wangi Labuhanbatu - Hasibuan, Milwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to see the results of the attraction, digital promotion, and facilities on the interest of tourists visiting the Taman Kelapa Pandan Wangi destination in Labuhanbatu Regency. The approach used is quantitative with a research population of 156 tourists, based on visit data in February 2025. The sample was taken using the Slovin formula with a random sampling technique, resulting in 112 respondents. The main instrument for data collection was a closed questionnaire with a Likert scale, supported by documentation and field observations. The results of the analysis show that partially, the tourist attraction variable has a positive and significant effect on interest in visiting. Likewise, digital promotion and facilities show a positive and significant contribution in increasing tourist interest. Simultaneous tests strengthen these findings, where the three independent variables together have a significant effect on tourist interest. These findings emphasize the importance of integrated management in developing tourist destinations. Strengthening the attraction through attraction innovation, optimizing digital media-based promotions, and providing adequate facilities are strategic elements to increase the competitiveness of destinations. In the context of local tourism, this not only encourages increased visits but also strengthens visitor loyalty. A development strategy that is oriented towards the quality of tourist experience and satisfaction is an important foundation in supporting the sustainability of the regional tourism sector holistically.